2011
DOI: 10.1111/j.1532-7078.2010.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Linguistic Study of Word-Mapping in 18- to 20-Month-Old Infants

Abstract: This study was designed to examine whether infants acquiring languages that place a differential emphasis on nouns and verbs, focus their attention on motions or objects in the presence of a novel word. An infant-controlled habituation paradigm was used to teach 18-to 20-month-old English-, French-, and Japanese-speaking infants' novel words for events. Infants were habituated to two word-event pairings and then presented with new combinations that involved a familiar word with a new object or motion, or both.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…In Katerelos et al (2010), Japanese-speaking children aged 1; 8 looked significantly longer at the agent switch trial but not at the action switch trial, indicating that they tended to map the novel word onto the agent when both the agent and action interpretations were available. recovered at the word switch trial) mapped novel words onto the action and not onto the agent.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In Katerelos et al (2010), Japanese-speaking children aged 1; 8 looked significantly longer at the agent switch trial but not at the action switch trial, indicating that they tended to map the novel word onto the agent when both the agent and action interpretations were available. recovered at the word switch trial) mapped novel words onto the action and not onto the agent.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, in the single word experiment (Katerelos et al, 2003(Katerelos et al, , 2010, the children recovered at both the word and the agent switch trials but not at the action switch trial, as shown in Figure 2. The results indicated that none of the effects were significant (ps>0 .…”
Section: R E S U L T Smentioning
confidence: 86%
See 1 more Smart Citation
“…What are the factors that influence children's ability to map words onto events? A hybrid theory of language development, the Emergentist Coalition Model (ECM), may help unpack the complexity of verb learning (Hollich et al, 2000;Katerelos, Poulin-Dubois, Oshima-Takane, 2011). The ECM suggests that children have access to a number of co-occurring cues for word learning but hone in on those cues at different developmental time points.…”
Section: How Children Map Verbs To Eventsmentioning
confidence: 99%
“…Even before infants begin to produce verbs in earnest, they have begun to form representations of the kinds of concepts underlying both noun (object‐based) and verb (action‐based) meaning. For example, in one experiment, infants were shown dynamic scenes (e.g., a novel cartoon creature jumping back and forth over a fence) while listening repeatedly to a novel word, presented alone (e.g., “Blick!”; Katerelos, Poulin‐Dubois, & Oshima‐Takane, ). At test, infants viewed this now‐familiar scene and a new scene in which either the participant object changed (e.g., a new creature jumping over a fence) or the action changed (e.g., the same creature now racing across a platform).…”
Section: New Cross‐linguistic Evidence From Infantsmentioning
confidence: 99%